Maternal and early‐life area‐level characteristics and childhood adiposity: A systematic review. (29th April 2019) - Wilding, Sam; Ziauddeen, Nida; Smith, Dianna; Roderick, Paul; Alwan, Nisreen A.
Summary: There is a cross‐sectional evidence that physical and social environments are linked to childhood adiposity. Evidence is scarce for the role of preconception, pregnancy, and early‐life area‐level characteristics in shaping childhood adiposity. We aimed to systematically review evidence for associations between physical and social environmental conditions experienced in these periods and childhood adiposity. Published literature was identified from the CINAHL, Embase, MEDLINE, and PsycINFO databases. Longitudinal studies linking an area‐level environmental exposure in the preconception, pregnancy, or early‐life (less than 1 year) periods and a measure of adiposity between the ages of 2 and 12 years were examined. Eight studies in the United States, Denmark, South Korea, United Kingdom, and Canada satisfied the inclusion criteria. Storm‐induced maternal stress, nitrogen oxides exposure, traffic noise, and proximity were associated with greater childhood adiposity. Frequent neighbourhood disturbances were associated with lower adiposity, while particulate matter exposure was associated with both higher and lower adiposity in childhood. Area‐level characteristics may play a role in the ongoing obesity epidemic. There is a limited evidence of longitudinal associations between preconception, pregnancy, and early‐life area‐level characteristics with childhood adiposity. Numerous factors that appear important in cross‐sectional research have yet to be assessed longitudinally, both individually and in combination.